Use of reconstruction plate and intramedullary pin for repair of a tibiotarsus fracture in a red-legged seriema (Cariama cristata, Linnaeus, 1766): Case report - Michelle Colpani Fernandes; André Luis Mota da Costa; Thais Fernanda da Silva Machado Camargo; Lourenço Candido Cotes; Flávia Paiffer; Luan de Souza Santos; Reinaldo Caetano Silva; Rodrigo Hidalgo Friciello Teixeira (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Car accidents are the main cause of death among wild birds in Brazil, especially in those with terrestrial habits, such as the red-legged seriema (Cariama cristata). These accidents keep increasing because of urbanization, making it important to present new treatments than can help decrease the number of deaths and bring welfare to the animal. In this case report, a wild red-legged seriema was found hurt nearby a driveway. Radiographs showed a multi-fragmentary fracture between proximal and medium thirds of the tibiotarsus. The fracture was successfully repaired with an intramedullary pin and a reconstruction plate, which are less likely to result in muscular atrophy and do not require a second surgical intervention as the external fixators do. In conclusion, this case report shows that an association of a Steinman intramedullary pin and a reconstruction plate can be a less disturbing yet sill effective option to treat multi-fragmentary fractures in free-living birds, especially long-legged ones.